2009
DOI: 10.1209/0295-5075/87/36003
|View full text |Cite
|
Sign up to set email alerts
|

Drops onto gradients of texture

Abstract: Hydrophobic microtextures on solids provide water repellency: drops hardly stick on these materials and bounce off after impacts. Here we achieved solids decorated with a texture of variable density. Impacting water drops were observed to bounce off obliquely, demonstrating a transfer of vertical momentum in the horizontal direction, after rebound. This allows us to understand why vibrated drops move on such surface: an asymmetric dewetting takes place for each cycle of the vibration, which leads to an increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 29 publications
3
121
1
Order By: Relevance
“…If the contact angle of a superhydrophobic surface can be varied across the surface any drops will tend to move toward the lower contact angle regions. [115][116][117] Also of interest is that, drops can be elongated in different ways by patterning the roughness of the surface anisotropically; some examples relevant to this review are aligned fibers 118 and anisotropically structured polymer surfaces. 119,120 In the study by Boduroglu et al, polyxylylene was deposited by angled vapor deposition and produced a carpet of angled fibers.…”
Section: Sticky and Slippery Repellent Surfacesmentioning
confidence: 99%
“…If the contact angle of a superhydrophobic surface can be varied across the surface any drops will tend to move toward the lower contact angle regions. [115][116][117] Also of interest is that, drops can be elongated in different ways by patterning the roughness of the surface anisotropically; some examples relevant to this review are aligned fibers 118 and anisotropically structured polymer surfaces. 119,120 In the study by Boduroglu et al, polyxylylene was deposited by angled vapor deposition and produced a carpet of angled fibers.…”
Section: Sticky and Slippery Repellent Surfacesmentioning
confidence: 99%
“…Inclination, compliance, and finite size of the leaves all amplify this asymmetry [19]. Drop impacts that yield asymmetric behaviors were also studied with (i) horizontal gradients of texture and wetting properties [45][46][47][48][49][50], (ii) varying inclination or tangential speed of the substrate [51][52][53], and (iii) nonaxisymmetric target shapes [54,55]. The relationship between liquid sheet asymmetry and droplet ejections was investigated for a stationary liquid sheet [56].…”
Section: Introductionmentioning
confidence: 99%
“…Polygonal lamellae and anisotropic jetting (Reyssat et al 2010;Tsai et al 2011) were generated by square and hexagonal post arrays. Graduated post arrays were used to impart horizontal momentum to rebounding drops (Reyssat et al 2009). Pearson et al (2012) recently reported greater D max parallel to regular microstructured ribs (2.25 mm wide, 40 mm apart) at We !c.…”
Section: Discussionmentioning
confidence: 99%
“…because viscous losses are low, and there is weak adhesion at the contact line (Tsai et al 2009(Tsai et al , 2011Marengo et al 2011;Pearson et al 2012). The first observations of asymmetric drop impacts on microfabricated SHSs have been made using square, hexagonal (Reyssat et al 2010;Tsai et al 2011) and graduated (Reyssat et al 2009) post arrays, and on grooved SHSs (Pearson et al 2012). Some asymmetric low velocity wetting has been observed on SHSs (Dorrer & Ru¨he 2006;Que´re´& Reyssat 2008;Marengo et al 2011;Shirtcliffe et al 2011;Wu et al 2011;Mele et al 2012;Pearson et al 2012), giving rise to attempts to obtain directional wetting using synthetic anisotropic microstructures (Dorrer & Ru¨he 2006;Rasilainen et al 2009).…”
Section: Introductionmentioning
confidence: 99%